2019
DOI: 10.1186/s13018-019-1319-2
|View full text |Cite
|
Sign up to set email alerts
|

Need for concomitant Akin osteotomy in patients undergoing Chevron osteotomy can be determined preoperatively: a retrospective comparative study of 859 cases

Abstract: Background The Chevron osteotomy is a frequently used surgical method for hallux valgus correction. This method is often combined with an Akin osteotomy. To date, clear guidelines for the implementation of an additional Akin osteotomy are missing. The purpose of this study was to elucidate the impact of concomitant phalangeal correction on the outcome after hallux valgus surgery and to define indication criteria for an additional Akin osteotomy. Methods Patients (859 fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 27 publications
2
13
0
3
Order By: Relevance
“…There was a significant increase (mean, 4.1 degrees, P < .001) in the a1-2 IMA from a mean of 10.9 degrees (range, 8-14) preoperatively to 15.0 degrees (range, [9][10][11][12][13][14][15][16][17][18][19] postoperatively. For the m1-2IMA, there was a significant decrease (mean, 4.6 degrees, P < .001) from a mean of 10.9 degrees (range, 8-14) preoperatively to 6.4 degrees (range, 1-11) postoperatively.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…There was a significant increase (mean, 4.1 degrees, P < .001) in the a1-2 IMA from a mean of 10.9 degrees (range, 8-14) preoperatively to 15.0 degrees (range, [9][10][11][12][13][14][15][16][17][18][19] postoperatively. For the m1-2IMA, there was a significant decrease (mean, 4.6 degrees, P < .001) from a mean of 10.9 degrees (range, 8-14) preoperatively to 6.4 degrees (range, 1-11) postoperatively.…”
Section: Resultsmentioning
confidence: 90%
“…The mean improvement of the m1-2IMA (4.6 degrees) and the mean postoperative m1-2IMA (6.4 degrees) is comparable to multiple prior studies evaluating DCO. 3,5,9,10,12,13,16,20,28,32 Similarly, the HVA was also noted to have significant improvement with a final average measurement of 8.5 degrees. This is consistent with the existing literature, 3,5,9,10,12,13,16,20,28,32 and expected given that the mechanical axis of the first metatarsal was used for the HVA measurement.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…It was found that the average contribution of the IPA to the total hallux valgus angle (HVA) is 28.3%, which should be considered for correction of hallux valgus. 25 Kaufmann et al 12 found a significantly improved correction of first-ray alignment in a combined chevron and Akin osteotomy compared to an isolated chevron osteotomy with a lower rate of recurrence. This finding was confirmed by another study of this group comparing isolated Scarf osteotomy with combined Scarf and Akin osteotomy (recurrence isolated Scarf 14.7% [n = 184] vs combined procedure 1.6% [n = 63]).…”
Section: Introductionmentioning
confidence: 99%
“…13 Hence, the authors recommend a combined procedure if a preoperative proximal to distal phalangeal articular angle of 8 degrees is present. 12,13…”
Section: Introductionmentioning
confidence: 99%